Paratriathlon classification: Peaking for Rio, preparing for Tokyo ...and beyond - Murray, S.; Martinez-Gramage, J.; Christophers, M.; Magkou, K.; Darby, G.; Angstadt, E. (Science + Triathlon 2015 World Conference, 2015)
Background: In 2011, after being accepted into the Rio 2016 Paralympic Games, the International Triathlon Union (ITU) embarked on the creation of an evidence based classification system. On the one hand, the basis of the IPC position regarding classification system in Paralympic Sport is to classify the impairments according to how much they affect the core activities of a specific sport or activity limitation. On the other hand, in contrast to the medical classification approach in which athletes compete in the same class for all sports, functional systems of classification are necessarily sport-specific, as one limitation may have a significant impact in one sport, while it may have a relatively small impact in another (Tweedy 2011). This unifying system has allowed a greater integration of the people with different limitations for equal participation in sport (Wilson 2009). The system was to determine the eligible impairment types for the sport of triathlon from the ten (10) recognized impairment types by the International Paralympic Committee, help set the minimum eligibility criteria and reflect the relation between impairment and activity limitation in order to minimise the impact of impairments on the outcome of the competition. Aim: The purpose of the project was to find a methodology of classification assessment to allocate athletes into triathlon sport classes according to the limitation caused by their impairment in the three disciplines: swim, bike and run, as well as the two transitions comprised in Triathlon. At the same time, identify the eligible impairment types and the MIC (minimum impairment criteria). Method: There were seven steps taken during the initial part of the research study: literature review, re-evaluation of the current ITU scorecard (including key body parts, their relevance, technical and novel tests), specific requirements for eligibility for athletes with neurological-related impairments, hypothesis testing, selection of the athletes for the study, data collection on individuals and statistical analysis. A significant amount of data was collected in order to validate the findings to implement the new classification system. In order to identify the most reliable manner to conduct classification assessments, the Research Group tried to identify the variables and tests (Functional Movement Screen, Manual Muscle Testing (Daniels & Worthingham), TUG and Functional Athlete Profile- sport specific and novel tests) with the highest correlation to time in competition. Pearson correlations were used for this purpose with the SPSS version 18 program. Conclusion: The Manual Muscle Testing and Functional Athlete Profile were the adopted methods in this first review of the new classification system to quantify the relation of impairment and activity limitation. The system will anyhow, be under constant review till Rio and beyond. Educational material has been developed and used in certification courses for new classifiers.